Evaluation of Three Cucurbitaceae Cultivars Resistant against Begomoviruses Based on Morphological Symptoms and Molecular Analysis - Subiastuti, Aprilia Sufi; Huda, Muhammad Syafi’atol; Daryono, Budi Setiadi (Jurnal Perlindungan Tanaman Indonesia, 2024)
Cucurbitaceae is a group of annual horticultural crops with high economic prospects and benefits. The Faculty of Biology, Universitas Gadjah Mada has developed several new cultivars within the Cucurbitaceae family, such as the melon cultivar 'Hikapel', watermelon 'Citra Jingga', and butternut squash 'Citra Laga'. However, development of these cultivars has been hindered by yellow disease, typically triggered by Begomovirus infection. This study aimed to determine the morphological symptoms of yellow disease, to detect Begomovirus infection using molecular approach, and assess resistance levels of the three Cucurbitaceae cultivars. The method involved observing morphological symptoms in plants and measuring plant height. The degree of symptom severity was then converted into a vulnerability index (VI). The symptomatic leaf samples were tested using Krusty and Homer primer to confirm the symptoms caused by Begomovirus. The PCR results were sequenced and analyzed using Maximum Likelihood method in MEGA 11. The results showed that symptoms included curling tip of leaves, yellow mosaic on the leaves, and stunted growth in some plants, which were suggested as Begomovirus infection. Based on the Vulnerability Index (VI), the watermelon cultivar 'Hikapel' was considered susceptible to Begomovirus infection (VI = 85%), while the yellow squash 'Citra Laga' was moderately susceptible (VI = 57.5%). However, the watermelon 'Citra Jingga' was considered moderately resistant to this infection (VI = 50%). The presence of DNA the Begomovirus at three species Cucurbitaceae were characterized by a 550 bp band. The 'Hikapel' melon and 'Citra Laga' butternut were infected with Tomato leaf curl New Delhi virus (ToLCNDV), while the ‘Citra Jingga’ watermelon were infected with Squash leaf curl Philippine virus (SLCuPV).